Sampling in Management Studies of Public Organizations: Elite Orientation Model vs. Multiple Informants Model - Dimitris Karastathis; Georgia Yfantidou; Stella Kormikiari; Dimitris Gargalianos; Antonia Kalafatzi (Ital Publication, 2021)
The selection of the sample in a survey constitutes a significant parameter for the research process. A disagreement of opinions is observed in the field of management between researchers regarding which sample fabricates better results in surveys administered in public organizations. Some of them support that only the senior levels of the management hierarchy should participate in (Elite Orientation Model), while others support the participation of representatives from all levels (Multiple Informants Model). A questionnaire was administered to people from the three levels of Hellenic Sport Federations (HSFs) management hierarchy (employees, directors/managers, Board members) in order to investigate their perception about the degree to which excellence processes (enablers / results) were implemented. The purpose of this paper was to investigate which is the most appropriate model, regarding the selection of participants in studies about the administration /management of public organizations. Statistically significant differences regarding their perceptions for the topic under investigation were revealed, which were directly related to their level in the hierarchy. It was concluded that in similar studies the Multiple Informants Model fabricates more reliable results. Doi: 10.28991/esj-2021-01272 Full Text: PDF